CERTAIN APPROACHES TO EFFICIENCY EVALUATION OF THE REGIONAL TB SERVICES - I. B. Geltser; K. I. Shаkhgeldyan; E. V. Krivelevich; V. I. Medvedev; M. Z. Ermolitskаya (Туберкулез и болезни лёгких)
The goal of the study is to perform the comprehensive assessment of the efficiency of regional TB services based on the analysis of certain indicators reflecting accessibility and quality of tuberculosis care.Subjects and Methods. This study used data of medical statistics on tuberculosis and demography. Processing and analysis were performed using Big Data, methods of descriptive statistics, correlation and cluster analysis.In Primorsky Kray, where TB situation is much worse compared to the overall situation in the Russian Federation, the quality of tuberculosis care differs significantly depending on the municipality. Based on the rates reflecting the burden of tuberculosis and treatment efficiency using hierarchical clustering and k-means, 4 clusters of municipalities were identified having different levels of the above rates. The availability of human resources for tuberculosis care was assessed for each of 4 clusters. It was found out that clusters with a high burden of tuberculosis were characterized by poor human resources availability for all the rates and vice versa. The results of the study allowed concluding that human resources availability for tuberculosis care was a crucial factor providing an impact on the efficiency of TB services performance.